Desempenho agronômico de cultivares de beterraba em função da adubação fosfatada - Silva, Gerlani Alves da (2017)
The absence of phosphorus in the soil can directly affect the quality and productivity of the plants; however, investigations under different doses of phosphorus are necessary and consequently an important tool for beet growers. With the objective of evaluating the and quality of beet cultivars as a function of phosphorus doses, an experiment was carried out at the Experimental Farm Rafael Fernandes, Alagoinha / Mossoró District (RN), from July to October of 2016. The experimental design was the one of randomized blocks in scheme factorial 4x4 with four replicates. The treatments consisted of the combination of four doses of phosphorus (0, 90, 180 and 270 kg ha-1 P2O5) and four beet cultivars (Early Wonder, Fortuna, Kestrel and Cabernet). The evaluated characteristics were dry mass of shoot and root; commercial, non-commercial and total root productivity; root classification, soluble solids total and percentage of white rings inside the root. Beet cultivars responded to phosphate fertilization, and the dose that maximized commercial productivity was 186 kg ha-1 of P2O5 for the cultivars Early Wonder (21.71 t ha-1) and Kestrel (22.59 t ha-1), 180 kg ha-1 of P2O5 for Cabernet (25.82 t ha-1) and 183 kg ha-1 of P2O5 for Fortuna (29.87 t ha-1). Regarding the efficiency and response to phosphate fertilization, the cultivars Cabernet and Fortuna were classified as non-efficient but responsive, whereas Early Wonder and Kestrel were classified as efficient but not responsive. Phosphorus did not influence solids content solubles and percentage of white rings in the root. The Kestrel cultivar presented higher solids content Soluble and Cabernet had lower percentage of white rings